Islamic Family Law in the Philippines: A Historical Survey - Ali, Anshari Pangaga (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Islamic Family Law in the Philippines: A Historical Survey